The Hypothesis of the Human iNKT/Innate CD8(+) T-Cell Axis Applied to Cancer: Evidence for a Deficiency in Chronic Myeloid Leukemia - Jacomet, Florence; Cayssials, Emilie; Barbarin, Alice; Desmier, Deborah; Basbous, Sara; Lefèvre, Lucie; Levescot, Anaïs; Robin, Aurélie; Piccirilli, Nathalie; Giraud, Christine; Guilhot, François; Roy, Lydia; et al. (Frontiers in Immunology, 2017)
We recently identified a new human subset of NK-like (KIR/NKG2A(+)) CD8(+) T cells with a marked/memory phenotype, high Eomesodermin expression, potent antigen-independent cytotoxic activity and the capacity to generate IFN-γ rapidly after exposure to pro-inflammatory cytokines. These features support the hypothesis that this new member of the innate T cell family in humans, hereafter referred to as innate T CD8(+) T cells, has a role in cancer immune surveillance analogous to invariant natural killer T (iNKT) cells. Here, we report the first quantitative and functional analysis of innate CD8(+) T cells in a physiopathological context in humans, namely chronic myeloid leukemia (CML), a well-characterized myeloproliferative disorder. We have chosen CML based on our previous report that IL-4 production by iNKT cells was deficient in CML patients at diagnosis, and considering the recent evidence in mice that IL-4 promotes the generation/differentiation of innate CD8(+) T cells. We found that the pool of innate CD8(+) T cells was severely reduced in the blood of CML patients at diagnosis. Moreover, like iNKT and NK cells, innate CD8(+) T cells were functionally impaired, as attested by their loss of antigen-independent cytotoxic activity and IFN-γ production in response to innate-like stimulation with IL-12+IL-18. Remarkably, as previously reported for IL-4 production by iNKT cells, both quantitative and functional deficiencies of innate CD8(+) T cells were at least partially corrected in patients having achieved complete cytogenetic remission following tyrosine-kinase inhibitor therapy. Lastly, direct correlation between the functional potential of innate CD8(+) T and iNKT cells was found when considering all healthy donors and CML patients in diagnosis and remission, in accordance with the iNKT cell-dependent generation of innate CD8(+) T cells reported in mice. All in all, our data demonstrate that CML is associated with deficiencies of innate CD8(+) T cells that are restored upon remission, thereby suggesting their possible contribution to disease control. More generally, our study strongly supports the existence of an innate CD8 T/iNKT cell axis in humans and reveals its potential contribution to the restoration of tumor immune surveillance.